Geochemistry of siltstones in the North Qilian Zhongbao–Mayinggou formations (Late Ordovician–Early Silurian): implications for paleoclimate, paleoweathering, and tectonic setting - Xia, Yu; Hou, Qian; Mou, Chuanlong (Frontiers in Earth Science, 2024)
The Late Ordovician–Early Silurian period witnessed the Phanerozoic mass extinction, glacial events, and volcanic events. Paleoweathering indexes chemical index of alteration (CIA), chemical index of weathering (CIW), and plagioclase index of alteration (PIA) indicated that the source area weathering changed from weak to moderate to intense. CIA values in the upper Zhongbao formation ranged from 66.71% to 73.97%, indicating a drier and colder climate. Upward, the CIA values on the bottom of the Mayinggou formation returned to the high value quickly (from 73.86% to 81.31%), suggesting that the ice age ended, the climate became warmer and wetter, and the sea level rose. The Al2O3–(CaO*+Na2O)–K2O triangular plots, Hf-La/Th, and SiO2–Al2O3/TiO2 bivariate plots inferred that the source of the siltstones in the two formations is mostly from the felsic igneous rocks. The samples from the Zhongbao–Mayinggou formations have chondrite-normalized rare earth element (REE) patterns similar to that of the North Qilian volcanic arc rocks. Geochemical discrimination plots displayed that the sediments of the Zhongbao–Mayinggou formations came from the active continental margin setting.